Methicillin-Resistant Staphylococcus aureus Secondary Infection as a Comorbid in Crusted Scabies Patient - Anggun Putri Yuniaswan; Arista Putri Rakhmana Sari (Universitas Wijaya Kusuma Surabaya, 2024)
Introduction: Crusted scabies (CS) is characterized by uncontrolled proliferation of mites up to thousands. Complications include glomerulonephritis, rheumatic fever, and secondary infection which can cause bacteremia and sepsis. This case report describes a case of CS that was hospitalized with secondary complications of MRSA infection. Case Presentation: A 44-year-old woman complained of thick scales and itching all over her body for 6 months. Complaints begin with reddish bumps between the fingers, toes, body, genitals, and scalp, accompanied by itching, especially at night. The patient took self-purchased corticosteroids for this complaint for 6 months. Dermatology status all over the body showed erythematous papules plaques with greenish-yellow scales, blackish crusts, hyperkeratosis, and excoriation, also erythematous base erosions and blackish crusts in the right thoracic region. Ectoparasite scrapping examination showed large amounts of Sarcoptes scabiei, eggs, and scybala, so the patient was diagnosed with Crusted scabies. A wound culture and nasal swab showed MRSA. The patient died of septic shock on day 12 of treatment. Discussion: Crusted scabies is a highly contagious form of scabies, characterized by thickening of the skin layer and crusts. Long-term corticosteroid consumption in this case caused a compromised immune response so that the number of mites multiplied rapidly and increased the risk of MRSA infection. MRSA mortality rates range from 5-60%. Conclusion: Ignored cases of scabies can develop into crusted scabies which have a high risk of secondary infection, such as MRSA which can cause serious morbidity and even mortality.